ANALISIS HALAL TOURISM MAKAM ORANG KAYO HITAM DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT BERBAK - Aulia maharani; Eja armaz hardi; M. maulana hamzah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The tourism sector is a sector that has many impacts and one of them is in the economic sector. Halal tourism is considered a new breakthrough to introduce and develop Indonesian tourism that upholds cultural and Islamic values. This research aims to analyze halal tourism at the Orang Kayo Hitam Cemetery, the welfare conditions of the community around the Orang Kayo Hitam Cemetery. The method used in this research is qualitative in the form of field research where this research goes directly into the field to obtain accurate and objective data. Research data was obtained by observation, interviews and also documentation of business actors around the Orang Kayo Hitam Cemetery. The results of the research show that the graves of the Black Kayo people have great potential for developing halal tourism. Community welfare is considered very good where the local community can take advantage of existing potential, and this can indirectly make the community's economic condition better than before.